2020
DOI: 10.1097/prs.0000000000006321
|View full text |Cite
|
Sign up to set email alerts
|

Should We Stick with Surgical Glues? The Incidence of Dermatitis after 2-Octyl Cyanoacrylate Exposure in 102 Consecutive Breast Cases

Abstract: Summary: Skin adhesives have become standard in wound closure as alternatives to traditional sutures or as sterile occlusive dressings after surgery of all types. The literature is replete with case reports of contact dermatitis following exposure to cyanoacrylate-based adhesives, such as 2-octyl cyanoacrylate. Nonetheless, it has been the impression of the senior author and others that the incidence of allergic and/or contact dermatitis is much higher than commonly considered. The authors prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Nigro et al recently evaluated a cohort of patients who underwent breast surgery with cyanoacrylate products. 17 Twelve patients developed significant dermatitis reactions. Two patients had previous known allergies to cyanoacrylate.…”
Section: Discussionmentioning
confidence: 99%
“…Nigro et al recently evaluated a cohort of patients who underwent breast surgery with cyanoacrylate products. 17 Twelve patients developed significant dermatitis reactions. Two patients had previous known allergies to cyanoacrylate.…”
Section: Discussionmentioning
confidence: 99%
“…5 CA glues, despite generally safe, can sometimes cause infection in the site where they are applied 6 or dermatitis. 7 An adverse event could be due to subject’s sensitivity to the active principle or to one of the excipients contained in the glue. Literature reports different prevalence of infection (up to a complete absence) based on the brand and formulation used.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanoacrylate glues are used as dressings or adjuncts to closure and can expedite closing times, lead to improved scars, and provide an antibacterial barrier to skin pathogens. [51][52][53] There are multiple reports of contact dermatitis as a result of cyanoacrylate glue products, [53][54][55][56][57] with rates ranging from 0.5% to 14%, and have been hypothesized to vary based on anatomic location due to skin thickness. 53,58 A prospective study of cosmetic and reconstructive breast surgery found 14% developed contact dermatitis, with allergy to cyanoacrylate confirmed by allergy scratch testing.…”
Section: Surgical Gluementioning
confidence: 99%
“…[51][52][53] There are multiple reports of contact dermatitis as a result of cyanoacrylate glue products, [53][54][55][56][57] with rates ranging from 0.5% to 14%, and have been hypothesized to vary based on anatomic location due to skin thickness. 53,58 A prospective study of cosmetic and reconstructive breast surgery found 14% developed contact dermatitis, with allergy to cyanoacrylate confirmed by allergy scratch testing. 53 Presentation is characterized by eczematous to urticarial dermatitis 5-14 days after surgery and can progress to a systemic response known as id reaction or auto-eczematization characterized by widespread macular/papular eruption and generalized pruritis.…”
Section: Surgical Gluementioning
confidence: 99%